INFLUENCE OF HEALTH PERSONAL HEALTH EDUCATION TO KNOWLEDGE STUDENTS PRAMUKA MEMBERS IN SMA PENCAWAN MEDAN - Pomarida Simbolon; Nagoklan Simbolon (Institute Of Computer Science (IOCS), 2019)
The first aid is a form of temporary relief to the victim as quickly and accurately as possible before obtaining more competent medical help to prevent the victim from becoming more severe with the aim of sustaining life, reducing disability numbers and providing a sense of security and comfort to the victim. Based on a preliminary survey, students of Scout members at SMA Pencawan did not know about first aid because they had never received health education about first aid. The purpose of the study is, to determine the effect of first aid health education to the knowledge of students / scout members about first aid in SMA Pencawan Medan. The population in the study were 30 scout members. The sampling technique in this study is the total sampling, where the number of samples is the same as the population. The research design is pre experiment using one-group pre-post test design. The data collection tool uses SAP and questionnaires. Data analysis using wilcoxon test, got pretest value of 14,17 and posttest 26,40 with p value = 0,000 (p <0,05). This research indicates that there is an influence of health education to the knowledge of students of Scout members in SMA Pencawan Medan. It is hoped that the school will invite the student members to play a role in doing first aid to handle cases of injuries in the school and community environment. Keywords: Health Education, Knowledge, First Aid